A review of electricity pricing in peninsular Malaysia: Empirical investigation about the appropriateness of Enhanced Time of Use (ETOU) electricity tarif - Sulaima, Mohamad Fani; Dahlan, Nofri Yenita; Mat Yasin, Zuhaila; Mohd Rosli, Marlinda; Omar, Zulkiflee; Hassan, Mohammad Yusri (Elsevier Ltd., 2019)
This paper presents the foundation of the Peninsular Malaysia's electricity market reform and development towards successful of Incentive Based Regulation (IBR) implementation, when revising also the Special Industry Tariff (SIT), Time of Use (TOU) and Enhanced Time of Use (ETOU) tariff. The Malaysian characteristics of Price Based Program (PBP) pointed out are compared with other countries across several continents. Since PBP benefits the energy providers in order to enhance power system efficiency, the effectiveness of consumer side strategies to gain benefit from PBP should be given attention too. In this study, investigation has been focused on one of the PBP which is ETOU tariff; with regard to the impact of this new tariff in communicating to selected real data energy profile for all commercial and industrial tariff types through congruent analysis. Without any effort towards load management as well as Demand Side Management (DSM) strategies implementation, the dedicative consumers' electricity bill has increased significantly to approximately 0.5%–12% during ETOU tariff shifting. In order to overcome this issue, a novel formulation by using simultaneous demand side management strategies such as valley filling, load clipping and load shifting for the ETOU tariff optimization is proposed. Meanwhile, the momentous simulation analysis results has demonstrated that major commercial and industrial consumers should find out for about 20%–50% of load management; by selecting PBP activities before they can switch to new tariff program.